Qualitative perspectives on COVID-19, interpersonal violence, and interventions to improve well-being from adolescent girls and young women in Kisumu, Kenya - Reed, Ruby E.; Omollo, Mevis; Odero, Isdorah; Awuonda, Eucabeth; Ochere, Peter; Ondeng’e, Ken; Kang, Jennifer L.; Altamirano, Jonathan; Barsosio, Hellen C.; Sarnquist, Clea (Frontiers in Reproductive Health, 2023)
Introduction: Adolescent girls and young women (AGYW) face substantial gender-based violence (GBV) worldwide. The COVID-19 pandemic and associated policies led to global increases in GBV, decreased access to resources, and disruptions of pathways to care. We aimed to understand the effects of COVID-19 on AGYW in Kisumu, Kenya, as well as identify possible interventions to mitigate those effects. Methods: Focus group discussions (FGDs) with AGYW aged 15-25 with a history of exposure to GBV. AGYW were split into age-matched groups; aged 15-19 for younger groups and 19-25 for older groups. Discussions focused on how COVID-19 affected experiences of GBV, mental healthcare, economic and social outcomes, and opportunities for interventions to mitigate negative impacts of COVID-19 and violence. Results: Five FGDs with 46 AGYW were completed in June-September 2021. AGYW described increases in all types of GBV, particularly sexual abuse and intimate partner violence. Early marriage and subsistence transactional sex also increased. AGYW described violence as both a cause and effect of poor economic, social and health consequences related to the pandemic. Notably, AGYW emphasized stress, lack of mental health support and worsening substance use as risk factors for violence, and discussed the deleterious mental health effects of violence – particularly in the wake of disruption of mental health services. COVID-19 disrupted referrals to violence-related services, with closures of both medical services and psychosocial services like support groups. AGYW reported believing that interventions focused on improving mental health as well as economic opportunities would be the most feasible and acceptable in mitigating the negative effects of COVID-19. Discussion: AGYW reported increases in all forms of GBV, and decreased access to services, during the COVID-19 pandemic. As there is no evidence that issues like violence and mental health challenges will quickly resolve, there is an urgent need to identify and implement interventions to mitigate these negative effects. Next steps of this work are to identify, implement, and ideally research, an appropriate intervention.